DEVELOPING THE CHARACTER PROFILE OF PANCASILA-BASED STUDENTS THROUGH PARENTING ACTIVITIES AT EARLY CHILDHOOD EDUCATION - Sholehah Yuliati; Ichsan Anshory; Erna Yayuk (Universitas Islam Negeri Mataram, 2025)
Character education is a crucial foundation for developing a competitive and integrated generation. The Pancasila Student Profile (P3) offers an alternative approach to instilling character values from an early age, encompassing six main dimensions (Kadir, 2023). Ki Hadjar Dewantara (1962) emphasised that family, school, and community, as the three centres of education, play a strategic role in shaping children's character, including through parenting activities. This study examines: (1) designing parenting activities to foster the character of the Pancasila Student Profile, (2) creative ideas in parenting programs to strengthen character values, and (3) internal and external obstacles in their implementation. The method used was a descriptive qualitative approach, involving informants from the principal, teachers, and parents. Data were obtained through observation, interviews, and documentation, then analysed using the Miles & Huberman model. The results show that the parenting program at KB Al Hidayah Pacul Permai incorporates structured planning, positive habit formation methods, role models, and parental involvement, along with creative initiatives such as Family Gatherings, Market Days, and Home Activities. Despite these obstacles, collaboration between schools and parents is key to the program's success.